2019
DOI: 10.9745/ghsp-d-19-00195
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Electronic Partogram: A Mixed-Method, Quasi-Experimental Study Among Skilled Birth Attendants in Kenya

Abstract: Use of the electronic partogram, a digital labor-support application, is associated with improved fetal outcomes and greater use of interventions to maintain normal labor compared to the paper partograph.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 21 publications
(28 reference statements)
0
28
0
Order By: Relevance
“…In Ethiopia, health care providers recognized that the e-partograph could reduce maternal and neonatal mortality, but staff shortages, lack of skills/competence, and lack of motivation were mentioned as barriers for partograph utilization [ 55 ]. Studies from Kenya and Tanzania found that even where e-partograph is acceptable and has high perceived ease of use, its feasibility in settings with high delivery load, staff shortages, and lack of infrastructure is limited [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, health care providers recognized that the e-partograph could reduce maternal and neonatal mortality, but staff shortages, lack of skills/competence, and lack of motivation were mentioned as barriers for partograph utilization [ 55 ]. Studies from Kenya and Tanzania found that even where e-partograph is acceptable and has high perceived ease of use, its feasibility in settings with high delivery load, staff shortages, and lack of infrastructure is limited [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The user rate of e-partogram showed three-fold increase (OR 3.31; 95 % CI, 2.04–5.38; p < 0.001) compared to the user rate with paper partogram. Similarly, a study from Kenya comparing 842 women monitored with e-partogram and 1042 women with paper partogram showed usage of e-partogram associated with a 56 % (95%CI, 27 %–73 %) lower likelihood of adverse fetal outcomes as compared to monitoring with paper partogram [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The electronic partograph releases audible reminders when clinical measurements are due, but the intervention developers and evaluators have not assessed contextual feasibility of WHO's recommendations for labour surveillance, which were adopted directly into the intervention. 29…”
Section: At the Global Levelmentioning
confidence: 99%